Adventuring Physics: Integration of Adventure Game and Augmented Reality Based on Android in Physics Learning - Rizki, Iqbal Ainur; Saphira, Hanandita Veda; Alfarizy, Yusril; Saputri, Aulia Dwi; Ramadani, Riski; Suprapto, Nadi (International Journal of Interactive Mobile Technologies (iJIM), 2023)
One of the difficulties in physics learning is the low motivation to learn because physics materials are considered complex, boring, and abstract for students. Therefore, this research developed an Augmented Reality (AR)-integrated game application "Adventuring Physics" based on android that can create more fun physics learning and provide concept visualization on abstract materials so that they become easier for students to understand. This study aims to develop a valid and practical application of Adventuring Physics games on physics learning. This research uses Research and Development (R&D) design to develop the application. This application has two main features: 'play games' and 'augmented reality'. Furthermore, the game's concept in this application is adapted to the physics materials. Meanwhile, the AR feature in this application can create visualizations in the form of 3D image projections of the material. The results of the validity assessment show that this application is declared valid, feasible, and reliable. In addition, the results of the practicality assessment show that this application is very practical. Thus, the app is worth applying in physics learning. This research has implications as an application of Adventuring Physics that can motivate students to learn physics, apply digital technology in education, and apply it to physics learning.